Assessing client-side protection impact on C+L+S multi-band optical networks with a GNPy-based planning tool - Guerreiro, R.; Cancela, L.; Rebola, J. (Optical Fiber Technology, 2025)
Multi-band (MB) transmission is a solution capable of increasing optical networks capacity and surpassing C-band transmission limitations. However, as more capacity is transported in these new MB networks, survivability and energy consumption issues become more relevant. This work investigates the impact of those issues in C+L+S MB optical networks using a tool based on the Gaussian noise Simulation in Python (GNPy) tool. The routing, modulation format and spectrum assignment (RMSA) algorithm provided in the GNPy tool is improved to take into account both client-side dedicated protection and inter-channel stimulated Raman scattering-Gaussian noise model. The protection level impact on the network performance is assessed by performing several RMSA studies on the German network for different protection levels and two blocking probabilities. Our results indicate that increasing the protection level by 25% leads to an 11% decrease in transported capacity and a 4% increase in spare capacity, with a 1 dBJpTbit increase in energy consumption per Tbit. Also, it is shown that these capacities become approximately stabilized above a 75% protection level. Despite the transported capacity in the C+L+S-band significantly increases compared to the C+L-band scenario, the energy consumption per Tbit remains almost the same in both scenarios.